L’investissement étranger et l’activité minière en Amérique latine. Les stratégies gouvernementales dans les conflits avec les compagnies minières - Maria Teresa Gutiérrez Haces (IdeAs)
The proliferation of Free Trade Agreements and Bilateral Investment Protection Agreements, which regulate relations between government and foreign companies, has sparked a number of lawsuits in the extractive sector against Latin American governments. Most of them have responded by implementing strategies to prevent, reduce and resolve all those conflicts arising from the operations of mining companies. This article aims at producing a tentative typology describing the different strategies that governments have designed to reconcile, neutralize, and, in some cases, cancel the application of a BIT or FTA, two instruments which are meant to regulate and discipline the relations between foreign companies and governments regarding investment. While some governments have modified their legislation, seeking to create an institutional structure that prevents conflicts; others have gone further and opted for the establishment of a moratorium on mining activities or declared part of their territory free of mining.